Huayllaquepa El sonido del mar en la tierra - Gudenios, Mónica L. (Revista Española de Antropología Americana, 2001)
This article presents an extract of the study of ceramic Moche trompets in conch-schell shape. Through this research we have verified the development of a skilled labour applied to the construction of objects used for good quality sound production.